2016
DOI: 10.18632/oncotarget.13484
|View full text |Cite
|
Sign up to set email alerts
|

Mammographic density: a potential monitoring biomarker for adjuvant and preventative breast cancer endocrine therapies

Abstract: Increased mammographic density (MD) has been shown beyond doubt to be a marker for increased breast cancer risk, though the underpinning pathobiology is yet to be fully elucidated. Estrogenic activity exerts a strong influence over MD, which consequently has been observed to change predictably in response to tamoxifen anti-estrogen therapy, although results for other selective estrogen receptor modulators and aromatase inhibitors are less consistent. In both primary and secondary prevention settings, tamoxifen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 98 publications
4
39
1
1
Order By: Relevance
“…However, these inhibitors have undesirable anti-angiogenic and other off-target effects when used systemically (Chhabra and Ferro 2020) and thus are unlikely MD-reducing agents to take forward to clinical trials. Tamoxifen reduces MD (Shawky, Martin et al 2017), however, its long-term use is associated with a wide range of potential side effects, some of which are intolerable (Thorneloe, Hall et al 2020). Both of these approaches are therefore potentially not feasible for MD reduction, although their mechanism of action provides important insight into how MD is governed, as our work alludes to, via the action of HPSE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these inhibitors have undesirable anti-angiogenic and other off-target effects when used systemically (Chhabra and Ferro 2020) and thus are unlikely MD-reducing agents to take forward to clinical trials. Tamoxifen reduces MD (Shawky, Martin et al 2017), however, its long-term use is associated with a wide range of potential side effects, some of which are intolerable (Thorneloe, Hall et al 2020). Both of these approaches are therefore potentially not feasible for MD reduction, although their mechanism of action provides important insight into how MD is governed, as our work alludes to, via the action of HPSE.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data identifying a positive association of HMD with lifetime exposure to estrogens is also a key finding to our understanding of MD in BC (Huo, Chew et al 2015). Estrogen unequivocally promotes MD, as evidenced by data showing alterations of MD with hormone contraceptives, hormone replacement therapy (Greendale, Reboussin et al 1999, Byrne, Ursin et al 2017, menopause (Stone, Warren et al 2009), and treatment with anti-estrogenic drugs (Chew, Huo et al 2014, Shawky, Martin et al 2017. Estrogen also influences cells within the tumour microenvironment, causing immunosuppression (Rothenberger, Somasundaram et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Oestrogenic activity strongly influences MD, and accordingly MD can change in response to tamoxifen anti-oestrogen treatment. However, the results obtained using other oestrogen receptor modulators or aromatase inhibitors have proven less conclusive [22]. A relation between adjuvant therapy and MD changes among women with BC have been described [23].…”
Section: Hormonal Therapy and Mammographic Densitymentioning
confidence: 99%
“…Other studies have shown that this decline in MD due to tamoxifen treatment results in a reduced BC risk when administered as chemopreventive treatment and in better BC outcomes (such as a lower risk of recurrence and lower rates of BC specific death) when in adjuvant settings [23]. Other studies have demonstrated that tamoxifen-associated MD decline translates into reduced breast cancer risk in the chemopreventive setting and improved breast cancer outcomes, including reduced risk of recurrence and breast cancer specific death, in the adjuvant settings [22,24]. Once BC is diagnosed, a diminution of MD has also been proposed as a prognostic marker for better long-term survival among patients that have received adjuvant therapy [25].…”
Section: Hormonal Therapy and Mammographic Densitymentioning
confidence: 99%
“…В крупных интервенционных рандомизированных исследовани-ях доказано, что тамоксифен, ралоксифен и ингиби-торы ароматазы анастразол и экземестан при профи-лактическом применении существенно снижают риск развития рака МЖ [34]. В ряде исследований убеди-тельно доказано, что тамоксифен при длительном как профилактическом, так и лечебном приеме умень-шает МГП; в связи с этим МГП рекомендуется ис-пользовать в качестве промежуточного биомаркера оценки эффективности препаратов для химиопрофи-лактики рака МЖ [32,35].…”
Section: опухоли женской репродуктивной системы Tumors Of Female Reprunclassified